2018
DOI: 10.1016/j.ijscr.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic biliopancreatic diversion for a morbidly obese patient with situs inversus totalis: Case report

Abstract: HighlightsLaparoscopic surgery in patients with situs inversus is technically challenging especially in morbid obese patients.This morbid obese patient underwent an uneventful laparoscopic bilio-pancreatic diversion.Any bariatric procedure can be done safely in morbid obese patients with situs inversus by an experienced bariatric surgeon in a specialized center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…The reversed anatomy in SIT patients, along with the associated vascular anomalies, was linked to an increased operative time [ 10 , 18 ]. There is also a non-consensus on the proper positioning of the operator and assistant beside the patient in the operative room, especially during laparoscopic surgeries, with some surgeons recommending reversing the operator and assistant positions to go along with the reversed anatomy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reversed anatomy in SIT patients, along with the associated vascular anomalies, was linked to an increased operative time [ 10 , 18 ]. There is also a non-consensus on the proper positioning of the operator and assistant beside the patient in the operative room, especially during laparoscopic surgeries, with some surgeons recommending reversing the operator and assistant positions to go along with the reversed anatomy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we present a case of gastric cancer and highlight the challenges faced by the surgical team in the removal of such cancer in SIT patients. In the literature, seven case reports could be found that described operations in adult SIT patients in Saudi Arabia with five reports describing cholecystectomies [ 5 - 9 ] and two reports describing bariatric surgeries [ 10 , 11 ], making this case report the first describing gastrectomy - and the first oncological procedure - in SIT patients in Saudi Arabia and the Gulf Cooperation Council (GCC) countries.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-three case reports were found after a PubMed literature search that included key search words of "situs inversus", "bariatric surgery", "anastomosis", "Roux-en-Y", "gastrectomy", and/ or "obesity". The results included 12 cases of Laparoscopic SG [6][7][8][9][10][11][12][13][14][15][16][17] 6 cases of Roux-en-Y gastric bypass, [8,[18][19][20][21][22] 2 cases of laparoscopic one-anastomosis gastric bypass, [23][24] 1 case of laparoscopic SG with duodeno-jejunal bypass, [25] 1 case of stomach intestinal pylorus sparing surgery (SIPS), [26] and 1 case of laparoscopic biliopancreatic diversion [27] . This can be seen in Figure 3.…”
Section: Methodsmentioning
confidence: 99%